Type 2 Diabetes Mellitus, Depression and Eating Disorders in Patients Submitted to Bariatric Surgery - Brandão, Isabel (2016)
Introduction: Obesity is associated with a great number of complications, including type 2 diabetes mellitus and psychiatric pathology. Bariatric surgery is the best solution to weight loss and improvement of complications in morbid obese patients. This study aims to analyze the evolution of type 2 diabetes mellitus and psychopathologic variables before and after bariatric surgery and assess the importance of different variables in weight loss.Material and Methods: This is a longitudinal study, which evaluates 75 patients before and after bariatric surgery (47 - LAGB – laparoscopic adjustable gastric band; 19 – RYGB – Roux-en-Y gastric bypass; 9 - sleeve) with a follow-up time between 18 and 46 months. A clinical interview and self report questionnaires were applied - Eating Disorder Examination questionnaire – EDE-Q and Beck Depression Inventory – BDI.Results: Results show an improvement in type 2 diabetes mellitus after surgery (χ2 (1) = 26.132, p < 0.001). There was not a significant improvement among psychiatric pathology when we controlled the analysis for the type of surgery. It was verified that type 2 diabetes mellitus, depression and eating disorders in post-operative period are associated with less weight loss. This model explains 27% of weight variance after surgery (R2 = 0.265) and it is significant F (3.33) = 2.981, p = 0.038.Discussion: Type 2 diabetes mellitus, psychiatric pathology and eating disorders after surgery influenced weight loss. It was not clear in what way this relation was verified, neither the relation that these metabolic and psychological variables may have during the postoperative period.Conclusion: Type 2 diabetes mellitus improved after surgery. Type 2 diabetes mellitus, depression and eating disorders influenced weight loss in the postoperative period. These variables did not influence weight loss in the preoperative period.